Green preparation of antibiotic nanoparticle complex as potential anti-biofilm therapeutics via self-assembly amphiphile–polyelectrolyte complexation with dextran sulfate - Cheow, Wean Sin (2013)
Nanoscale antibiotic delivery has emerged as a promising therapeutic means to treat lung biofilm infection owed to its sputum penetrating ability. Due to the high antibiotic dosage requirement in anti-biofilm therapy, the most suitable formulation for this purpose is the antibiotic nanoparticles themselves, instead of the more extensively studied antibiotic-loaded nano-carriers, which often exhibit low drug loading. The present work details the preparation and characterization of antibiotic nanoparticle complex (or nanoplex) by self-assembly amphiphile–polyelectrolyte complexation process. Ofloxacin (OFX) and levofloxacin (LEV) are used as the antibiotics with dextran sulfate (DXT) as the polyelectrolyte. The nanoplex possesses high drug loading (up to 80%) and size < 400 nm ideal for sputum penetration. Unlike existing methods to prepare drug nanoparticles, the present method is fast, energy-minimal, solvent-free, and highly efficient as manifested in nearly 100% of drug is transformed into nanoplex. The effects of drug-to-polyelectrolyte charge ratio, pH, drug, and salt concentrations on the nanoplex characteristics (i.e. size, stability, drug loading) are investigated from which the optimal preparation conditions have been identified. Higher complexation efficiency and stronger agglomeration tendency are observed for LEV nanoplex owed to its higher hydrophobicity. The antibiotics are completely released from the nanoplex in aqueous salt solution within 3 h and their antimicrobial activity is preserved upon complexation. The nanoplex is readily transformed into amorphous dry powders that remain stable after one-month storage owed to the high glass transition temperature. The antibiotic nanoplexes are highly charged enabling their subsequent functionalization for targeted delivery and controlled drug release purposes.